2019
DOI: 10.1177/2041669519840047
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging Findings on Amodal Completion: A Review

Abstract: Amodal completion is the phenomenon of perceiving completed objects even though physically they are partially occluded. In this review, we provide an extensive overview of the results obtained from a variety of neuroimaging studies on the neural correlates of amodal completion. We discuss whether low-level and high-level cortical areas are implicated in amodal completion; provide an overview of how amodal completion unfolds over time while dissociating feedforward, recurrent, and feedback processes; and discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 109 publications
(344 reference statements)
2
31
0
Order By: Relevance
“…In amodal completion, on the other hand, the completed parts are not subjectively visualized—which is why it is amodal—but are still visually represented, giving rise to a visual sense of presence of occluded figures ( Fig. 1B; Michotte and Burke 1951 ; van Lier and Gerbino 2015 ; Thielen et al 2019 ).…”
Section: If the Relevant Changes In C Are Intrapermentioning
confidence: 99%
“…In amodal completion, on the other hand, the completed parts are not subjectively visualized—which is why it is amodal—but are still visually represented, giving rise to a visual sense of presence of occluded figures ( Fig. 1B; Michotte and Burke 1951 ; van Lier and Gerbino 2015 ; Thielen et al 2019 ).…”
Section: If the Relevant Changes In C Are Intrapermentioning
confidence: 99%
“…The recent literature on AC includes, besides phenomenological and psychophysical studies (among others Ekroll et al, 2018;Øhrn et al, 2019;Peta et al, 2019;Scherzer & Ekroll, 2015;Scherzer & Faul, 2019; for a partial review, see van Lier & Gerbino, 2015), philosophical discussions that elucidate the theoretical impact of empirical research on amodal phenomena (Briscoe, 2018;Brown, 2018;Nanay, 2018;Orlandi, 2014), animal research on recognition of amodally completed shapes (Pepperberg, 2017;Pepperberg & Nakayama, 2016), as well as neural models of pattern completion (Tang & Kreiman, 2017). The fastgrowing neuroscientific evidence relevant to AC and related processes has been reviewed by Thielen et al (2019). As regards artificial vision, some computational models embody AC processes (Follman et al, 2018;Oliver et al, 2016;Zhu et al, 2017), while occasional references to AC are found in the broader literature on object recovery from images with missing regions, not necessarily due to occlusion (Ehsani et al, 2017;Guo et al, 2018;Han et al, 2017;Harary et al, 2014;Hueting et al, 2017;Li & Malik, 2016;Mavridis et al, 2015;Oliver et al, 2017;P erez et al, 2016;Shao et al, 2014).…”
mentioning
confidence: 99%
“…The recent literature on AC includes, besides phenomenological and psychophysical studies (among others Ekroll et al., 2018; Øhrn et al., 2019; Peta et al., 2019; Scherzer & Ekroll, 2015; Scherzer & Faul, 2019; for a partial review, see van Lier & Gerbino, 2015), philosophical discussions that elucidate the theoretical impact of empirical research on amodal phenomena (Briscoe, 2018; Brown, 2018; Nanay, 2018; Orlandi, 2014), animal research on recognition of amodally completed shapes (Pepperberg, 2017; Pepperberg & Nakayama, 2016), as well as neural models of pattern completion (Tang & Kreiman, 2017). The fast-growing neuroscientific evidence relevant to AC and related processes has been reviewed by Thielen et al. (2019).…”
mentioning
confidence: 99%
“…The illusion of absence is reminiscent of the well-known phenomenon of amodal completion ( Figure 1C and D ) because it also refers to a curiously compelling experience of occluded regions in a visual scene. Amodal completion refers to experiences of complete objects partially hidden behind an occluder, which are particularly compelling although only a few fragments of the object are directly visible ( Kanizsa, 1985 ; Michotte et al., 1964 ; Scherzer & Faul, 2019 ; Thielen et al., 2019 ; Van Lier & Gerbino, 2015 ). Figure 1D , for instance, evokes a very compelling experience of a single long finger, rather than the two separate fingers, which are aligned behind the cylinder ( Figure 1C ).…”
mentioning
confidence: 99%